Improving brand equity. Issue 10 (14th September 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings – A growing perception among many consumers is that brands and products are becoming increasingly more homogenous. Firms thus face an even greater challenge in the quest to make their offerings stand out from the crowd. Given the fiercely competitive landscape, the importance of brand equity cannot be overstated. High levels of equity indicate a strong brand that will be able to make its presence felt in the marketplace. Brand equity is often conceptualized as incorporating brand associations, brand loyalty, brand awareness and perceived quality dimensions. Brand associations are regarded as particularly influential. Consumers form these associations based on their knowledge and experience of the brand. Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.